PENGARUH TIM KERJA, KEPRIBADIAN, DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMA NEGERI DI KABUPATEN SINTANG - Asnol, Uray Bujang (Journal of Education Research in Administration and Management (JERAM), 2017)
THE EFFECT OF TEAMWORK, PERSONALITY, AND WORK MOTIVATION TOWARD PUBLIC HIGH SCHOOL TEACHER’S PERFORMANCE IN SINTANG DISTRICT       Uray B. Asnol Program Pasca Sarjana Universitas Negeri Jakarta Email : uray.asnol@gmail.com         Abstract   This study aims to investigate a direct positive effect of teamwork, personality, and work motivation toward public high school teacher’s performance in Sintang District. A survey method was employed in this quantitative study involving 193 teachers as respondents. A testing instrument was conducted prior to hypothesis test by means of path analysis. Findings show that: (1) teamwork variable has a direct positive effect toward teachers’ performance with coefficient value of 0.209; (2) personality variable has a direct positive effect toward teachers’ performance with coefficient value of 0.585; (3) work motivation has a direct positive effect toward teacher’s performance with coefficient value of 0.731; (4) teamwork variable has a direct positive effect toward work motivation with coefficient value of 0.126; and (5) personality variable has a direct positive effect toward work motivation with coefficient value of 0.647.   Keywords: Teamwork, Personality, Work Motivation, Teacher’s Performance